Application of zebrafish in the study of the gut microbiome. Issue 4 (12th April 2022) - Zhong, Xiaoting; Li, Jinglin; Lu, Furong; Zhang, Jingjing; Guo, Lianxian
Abstract: Zebrafish ( Danio rerio ) have attracted much attention over the past decade as a reliable model for gut microbiome research. Owing to their low cost, strong genetic and development coherence, efficient preparation of germ‐free (GF) larvae, availability in high‐throughput chemical screening, and fitness for intravital imaging in vivo, zebrafish have been extensively used to investigate microbiome‐host interactions and evaluate the toxicity of environmental pollutants. In this review, the advantages and disadvantages of zebrafish for studying the role of the gut microbiome compared with warm‐blooded animal models are first summarized. Then, the roles of zebrafish gut microbiome on host development, metabolic pathways, gut‐brain axis, and immune disorders and responses are addressed. Furthermore, their applications for the toxicological assessment of aquatic environmental pollutants and exploration of the molecular mechanism of pathogen infections are reviewed. We highlight the great potential of the zebrafish model for developing probiotics for xenobiotic detoxification, resistance against bacterial infection, and disease prevention and cure. Overall, the zebrafish model promises a brighter future for gut microbiome research. Abstract : Owing to their unique attributes, zebrafish have been harnessed as a powerful model for investigating host‐microbiome interactions using diverse techniques. In this review, the roles of zebrafish gut microbiome on their host development, gut‐brain axis, immune responses and metabolic pathways are summarized. Their applications on the toxicological assessment of environmental pollutants, the exploration of the pathogenic infection process, and the applications of probiotics are also reviewed.